Scott on the German stage: Reinhard Goering's Sudpoleexpedition des Kapitan Scott - Nielsen, Hanne (2012)
Much has been written about Robert F. Scott as an English barometer,l but little attention has been given to foreign views of the man or to relevant texts in other languages. This essay will examine Reinhard Goerings 1930 play Südpolexpedition des Kapitän Scott, a German Expressionist work based on' Captain Scott's 1911-12 expedition to the South Pole. With Goering's play, Scott's story was put on the public stage for the first time.2 There is a shortage of literature in the English language on this text and on German perspectives on exploration of the South Pole in general. German literary criticism is also thin on the ground, with most works focusing on Goering's earlier play Seeschlacht (1918). Scott's journals were available in German, but were not accompanied by the same cultural aura of awe as in Scott's homeland. For German audiences of the Weimar Republic the idea of sacrifice remained attractive in a time of austerity post World War I, while national pride was of less importance. German perspectives were also different from British ones due to social and political differences and a greater remoteness from events. Much has been written about Robert F. Scott as an English barometer,l but little attention has been given to foreign views of the man or to relevant texts in other languages. This essay will examine Reinhard Goerings 1930 play Südpolexpedition des Kapitän Scott, a German Expressionist work based on' Captain Scott's 1911-12 expedition to the South Pole. With Goering's play, Scott's story was put on the public stage for the first time.2 There is a shortage of literature in the English language on this text and on German perspectives on exploration of the South Pole in general. German literary criticism is also thin on the ground, with most works focusing on Goering's earlier play Seeschlacht (1918). Scott's journals were available in German, but were not accompanied by the same cultural aura of awe as in Scott's homeland. For German audiences of the Weimar Republic the idea of sacrifice remained ...